2015
DOI: 10.1089/jmf.2013.3135
|View full text |Cite
|
Sign up to set email alerts
|

Khz (Fusion Product of Ganoderma lucidum and Polyporus umbellatus Mycelia) Induces Apoptosis in Human Colon Carcinoma HCT116 Cells, Accompanied by an Increase in Reactive Oxygen Species, Activation of Caspase 3, and Increased Intracellular Ca2+

Abstract: Khz (a fusion mycelium of Ganoderma lucidum and Polyporus umbellatus mycelia) is isolated from ganoderic acid and P. umbellatus and it exerts antiproliferative effects against malignant cells. However, no previous study has reported the inhibitory effects of Khz on the growth of human colon cancer cells. In the present study, we found that Khz suppressed cell division and induced apoptosis in HCT116 cells. Khz cytotoxicity was measured using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…These findings suggested that Khz induces apoptosis in A549 human lung cancer cells by generating reactive oxygen species and decreasing the mitochondrial membrane potential (23). In addition, it has been suggested that Khz induces apoptosis in human colon carcinoma HCT116 cells, accompanied by an increase in ROS, the activation of caspase 3 and increased intracellular Ca 2+ (24). In addition, our previous study demonstrated that crude polysaccharide extract obtained from the fusion of G. lucidum and P. umbellatus mycelia induces apoptosis by increasing intracellular Ca 2+ levels and activating the P38 and NADPH oxidase-dependent generation of reactive oxygen species in SNU-1 cells (25).…”
Section: Discussionmentioning
confidence: 90%
“…These findings suggested that Khz induces apoptosis in A549 human lung cancer cells by generating reactive oxygen species and decreasing the mitochondrial membrane potential (23). In addition, it has been suggested that Khz induces apoptosis in human colon carcinoma HCT116 cells, accompanied by an increase in ROS, the activation of caspase 3 and increased intracellular Ca 2+ (24). In addition, our previous study demonstrated that crude polysaccharide extract obtained from the fusion of G. lucidum and P. umbellatus mycelia induces apoptosis by increasing intracellular Ca 2+ levels and activating the P38 and NADPH oxidase-dependent generation of reactive oxygen species in SNU-1 cells (25).…”
Section: Discussionmentioning
confidence: 90%
“…It is not quite clear how overexpression or dysregulation of ANO1 contributes to cancer development. To date, evidence has been accumulated indicating that chloride channels are important for control of transepithelial transport for ion homeostasis and cell volume regulation, which is integral to regulation of cell-cycle progression and proliferation [ 19 , 21 ]. Cell-cycle progression is critically dependent on cell volume in which profound alterations in volume regulation can lead to the generation of apoptosis-resistant cells [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, upregulation of chloride intracellular channel 1 (CLlC1) is involved in colon cancer cell migration and invasion through mediating regulatory volume decrease (RVD) mechanism [ 18 ]; and overexpression of chloride channel3 (ClC3) contributes to multiple human carcinomas such as glioma, lung, breast, and cervical tumors [ 19 ]. It has also been reported that the rise in intracellular calcium occurring during hypotonic challenge is related to RVD and involved with cancer apoptosis, indicating the interplay between calcium homeostasis and volume homeostasis [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ANO1 gene was first discovered in gastric stromal cancer and was initially named DOG1 (24). ANO1, as an ion channel, has a crucial role in sensing and transmitting extracellular signals to the intracellular machinery of epithelial cells, and a dysfunction of ANO1 may be involved in the development and progression of cancer of the epithelium by causing alterations of ion homeostasis and volume regulation (25,26). The ANO1 gene is involved in the development of cancer based on regulating intracellular free Ca 2+ levels (12,27).…”
Section: Discussionmentioning
confidence: 99%